Development of A Biotechnology Encyclopedia Based on Scientific Literacy to Improve Students' Scientific Literacy Abilities Unimed Biology Education Program - Sri Agustiani; Idramsa Idramsa; Ely Djulia (Green Publisher Indonesia, 2024)
The research aimed to assess the Biotechnology Encyclopedia's suitability as a learning resource for Biotechnology students, involving material, design, and learning experts. Developed using the ADDIE model, the study included sixth-semester students from the Biology Education Program at Medan State University. Sampling involved 56 students selected through simple random sampling. Data collection utilized questionnaires, tests, and interviews, analyzed quantitatively and qualitatively. Material and design experts rated the encyclopedia positively but suggested minor revisions, with 72% and 86% respectively in the